Perlindungan Hukum Terhadap Korban Revenge Pornografi Dalam Penyebaran Vidio Melalui Media Sosial - Muhammad Khadafi; Dedek Gunawan (Lex Justitia, 2026)
Revenge pornography refers to the act of disseminating sexually explicit photos and videos for the purpose of revenge. This act can have serious consequences for victims, including emotional, mental, and social impacts. Victim protection can be achieved through two mechanisms: direct and indirect. Indirect protection tends to provide emotional or psychological support. This research uses a normative juridical approach. Data collection was conducted using literature and documentation studies, followed by analysis. The literature review encompassed various techniques, including searching for references in books, e-books, journals, and other academic works, to establish linkages between theories and create an organized conceptual framework. Legal protection for women who experience revenge porn. Other protective measures include efforts to reduce the distribution of the victim's inappropriate material to prevent it from reaching more people. This can be done by communicating with communities where the victim's content is shared and blocking access to sites that disseminate the victim's material. Recommendations in this study highlight the importance of providing support to victims by guaranteeing their rights, including compensation, restitution, health support, counseling, legal aid, and information on case progress.